83.6k views
1 vote
What is the complete factorization of x2 − 6x + 9?

2 Answers

4 votes

Answer:

(x-3)²

Explanation:

User Savanna
by
5.2k points
4 votes

Answer:

The factors are (x-3) and (x-3)

Given:


x^(2)-6 x+9

Explanation:

In this problem, we need to find the factors which is on multiplying the factor we will get the equation.


\Rightarrow x^(2)-6 x+9

Now, we need find the sum of the coefficient of ‘x’ and product of the constant.

The coefficient of ‘x’ is written as:


\Rightarrow x^(2)-3 x-3 x+9

Now, we need to find the common multiply and divide the equation into two,


\Rightarrow x(x-3)-3(x-3)


\Rightarrow(x-3)(x-3)


\therefore(x-3)^(2)

Thus, the factor is formed which is multiplied to give the equation given in the question.

User Marcos Basualdo
by
5.5k points